Socioeconomic status and risk of kidney dysfunction: The Atherosclerosis Risk in Communities Study - Vart, P; Grams, M; Ballew, S; Woodward, M; Coresh, J; Matsushita, K (Oxford University Press, 2018)
Background: There is a strong evidence of association between socioeconomic status (SES) and end stage renal disease (ESRD). However, the association of SES with risk of chronic kidney disease (CKD) and rate of change in kidney function is unclear. Methods: In this prospective cohort study of 14,086 participants with eGFR ≥60 ml/min/1.73 m2 at baseline in the Atherosclerosis Risk in Communities Study (1987-1989) were examined for the association of annual household income, educational attainment and neighborhood deprivation with incident ESRD, incident CKD, and change in eGFR that was assessed using four eGFR measurements over ~23 years. Results: A total of 432 participants developed ESRD and 3,510 developed CKD over a median follow-up time of ~23 years. After adjustment for demographics and baseline eGFR, hazard ratio (HR) for incident ESRD was 1.56 (1.22-1.99) in medium and 2.30 (1.75-3.02) in low income, p-trend<0.001, and for CKD was 1.10 (1.01-1.20) in medium and 1.30 (1.17-1.44) low income, p-trend<0.001. In fully adjusted model, HR for ESRD was 1.33 (1.03-1.70) in medium and 1.50 (1.14-1.98) in low income, p-trend=0.003 and for CKD was 1.01 (0.92-1.10) in medium 1.04 (0.93-1.16) in low income, p-trend=0.50. eGFR decline was 5% and 15% steeper in medium and low income, respectively, after full adjustment, (p-trend<0.001). Results were similar when educational attainment and neighborhood deprivation were assessed. Conclusions: SES (annual household income, educational attainment, or neighbourhood deprivation) was associated not only with ESRD risk but also with eGFR decline though the association with CKD appeared weaker.